The IEEE 802.11g standard for high data rate WLANs. - Vassis, D. (IEEE Network : the magazine of global information exchange)
Continuous WLAN public acceptance comes with increasing demand for provision of higher data rates. Building on this context, the IEEE published the IEEE 802.11g standard for providing data rates of up to 54 Mb/s at the 2.4 GHz band. This article presents the new features of IEEE 802.11g and, using an open source C++-based simulation tool, evaluates both the performance and effectiveness of these features compared to the older IEEE 802.11 standard versions.